Assessment of the Concentrations of some Heavy Metals in some Vegetables Traded in the Local Market in Sebha City - Libya - Iessa, Kaes Rateb; Hamdan, Mohammed (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Consuming vegetables as food offers rapid and least means of providing adequate vitamins, minerals, and fibers. Vegetables used as food include those used in making soups or as integral parts of the primary sources of a meal. Leafy vegetables occupy a significant place in the human diet. Environmental exposure to heavy metals is a well-known risk factor for human health. The concentration of the heavy metals (Cu, Pb, Cd, and Cr) in vegetables from the Sebha market was determined using Atomic Absorption Spectroscopy AAS). In the Sebha local market, different vegetable types from different locations are marketed. Therefore this investigation was conducted to study the state of the accumulation of some heavy metals such as Cu, Cd, Pb and Cr. in some selected vegetables which include Solanum tuberosum (Potatoes), Allium cepa L. (Onion), Daucus Corota L. (Carrot), Cucurbita Pepo (Courgette), Solanum melongena L. (Eggplant), Lactuca sativa L. (Lettuce), Petroselinum crispum (mill.) Nym. (Parsley) and Spinacea oleracea (Spinach). The mean levels of these heavy metals ranged from 0.0-0.03, 0.0-2.36 and 0.0.0-8.13. ppm for Pb, Cd, and Cr. respectively. Among the vegetables studied, Cd and Cr exceeded the allowable limits recommended by WHO/FAO in some vegetables, whereas Cu and Pb concentrations are under the detectable limit. Statistical analysis shows a positive correlation between Cd and Cr at 0.01 and between Cd and Cr, Cd and Pb at 0.05.